Reconversion of Mono-Industrial Urban Areas (Case Study – Beclean City) - BOȚAN, Cristian Nicolae; PAVEL, Ion-Horațiu; FONOGEA, Silviu-Florin; GLIGOR, Viorel (Studia Universitatis Babeș-Bolyai Geographia, 2024)
Reconversion of Mono-Industrial Urban Areas (Case Study – Beclean City). Following the collapse of the communist regime in Romania, the country’s economy went through deep transformations, which negatively impacted the standard of living of the population. The closure of a large number of industrial enterprises overwhelmed the Romanian cities, and its impact was felt more intensely in the small, mono-industrial urban areas: since many of these had been established around these companies, their very existence was threatened by the closures. The city of Beclean is a typical example of such a mono-industrial settlement, which started facing difficulties with the decline of its metallurgical industry. In its search for life saving ideas, the local government decided to focus on the tourism potential of the area, as evidenced by the fact that all the projects under implementation in the city aim at developing this sector.